Effectiveness and safety of direct oral anticoagulants in patients with cancer associated venous thromboembolism. Issue 202 (June 2021) - Douros, Antonios; Filliter, Christopher; Azoulay, Laurent; Tagalakis, Vicky
Abstract: Introduction: Real-world evidence on the effects of direct oral anticoagulants (DOACs) in patients with cancer associated venous thromboembolism (VTE) is limited. Thus, our population-based cohort study aimed to assess the effectiveness and safety of DOACs compared to the standard of care low-molecular-weight heparin (LMWH) in this vulnerable population. Materials and methods: Using linked administrative healthcare databases from the province of Québec, Canada, we identified patients with incident VTE from 2012 to 2015 and a cancer diagnosis in the year before the VTE, who initiated treatment with anticoagulants within 30 days after the VTE. Using an active comparator new-user design with an as-treated exposure definition, we compared use of DOACs with use of LMWH. Cox proportional hazards models estimated adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) of recurrent VTE, major bleeding, and all-cause mortality. In secondary analyses, we stratified by age and sex. Results: Overall, 4438 patients with cancer associated VTE initiated treatment with anticoagulants (513 DOACs, 2698 LMWH). During a median follow-up of 0.3 years, and compared with LMWH, DOACs were associated with a decreased risk of recurrent VTE (HR, 0.54; 95% CI, 0.36–0.82) and major bleeding (HR, 0.54; 95% CI, 0.31–0.96). We also observed a decreased risk of all-cause mortality with DOACs compared with LMWH (HR, 0.14; 95% CI, 0.09–0.22). Age and sex did not modify the associations. Conclusions: DOACs were associated with improved effectiveness and safety compared with LMWH in patients with cancer related VTE. Unmeasured confounding probably contributed to our findings on all-cause mortality. Highlights: 4438 patients with cancer associated VTE initiated treatment with anticoagulants. DOACs were compared to the standard of care LMWH. DOACs were associated with decreased risks of recurrent VTE and major bleeding. Unmeasured confounding probably contributed to the decreased risk of all-cause mortality with DOACs.